Multi-level marketing from Islamic perspectives - Ahmad Razimi, Mohd Shahril; Romle, Abd Rahim; Yahya, Ummu Noor Habibah (IDOSI Publications, 2017)
Multi-Level Marketing (MLM) has been one of the controversial businesses in this modern business. It is because there are some of MLM’s activities that give the bad impact to the practitioners due to the hidden strategy from the top management in this business.The real purpose from this business activities is to generate income especially for an individual which it can help them to add an extra income so that they can improve their standards of living